Ash Deposition Triggers Phytoplankton Blooms at Nishinoshima Volcano, Japan - Liam J. Kelly; Kristen E. Fauria; Tushar Mittal; Jan El Kassar; Ralf Bennartz; David Nicholson; Ajit Subramaniam; Ashok Kumar Gupta (Geochemistry, Geophysics, Geosystems, 2023)
Abstract Volcanoes that deposit eruptive products into the ocean can trigger phytoplankton blooms near the deposition area. Phytoplankton blooms impact the global carbon cycle, but the specific conditions and mechanisms that facilitate volcanically triggered blooms are not well understood, especially in low nutrient ocean regions. We use satellite remote sensing to analyze the chlorophyll response to an 8‐month period of explosive and effusive activity from Nishinoshima volcano, Japan. Nishinoshima is an ocean island volcano in a low nutrient low chlorophyll region of the Northern Pacific Ocean. From June to August 2020, during explosive activity, satellite‐derived chlorophyll‐a was detectable with amplitudes significantly above the long‐term climatological value. After the explosive activity ceased in mid‐August 2020, these areas of heightened chlorophyll concentration decreased as well. In addition, we used aerial observations and satellite imagery to demonstrate a spatial correlation between blooms and ash plume direction. Using a sun‐induced chlorophyll‐a fluorescence satellite product, we confirmed that the observed chlorophyll blooms are phytoplankton blooms. Based on an understanding of the nutrients needed to supply blooms, we hypothesize that blooms of nitrogen‐fixing phytoplankton led to a 1010–1012 g drawdown of carbon. Thus, the bloom could have significantly mediated the output of carbon from the explosive phase of the eruption but is a small fraction of anthropogenic CO2 stored in the ocean or the global biological pump. Overall, we provide a case study of fertilization of a nutrient‐poor ocean with volcanic ash and demonstrate a scenario where multi‐month scale deposition triggers continuous phytoplankton blooms across 1,000s of km2.